Liner shipping operation under emission reduction measures - Hu, Xinyue (Nanyang Technological University, 2021)
Shipping is amongst the most important transport modes as it is a cost-effective mean to transport large volumes of cargoes world-widely. According to statistics, more than 87% of the world's trades are transported by sea and about 300,000 new containers are added to the global fleet annually. However, as shipping is gaining popularity, according to the International Maritime Organization (IMO), the total amount of ocean vessel emissions will surge by 2–3 times by 2050 as international trade increases, and research has shown that container ships emit more Green House Gas (GHG) than most other ocean vessel classes (Corbett et al, 2009), contributing more to such adverse impact. In order to impose stricter regulations to reduce vessel emissions, the MARPOL Annex VI was revised by the International Maritime Organization (IMO). From January 1 2020 onwards, for any fuel used onboard, the global sulfur must be reduced to 0.5%. There are three options for vessels: to continue to operate on high sulfur fuel oil but install sulfur scrubbers, to switch to marine gas oil (MGO) or to consider alternative fuel types such as methanol. Vessels may also choose slow-steaming for higher fuel efficiency and lower exhausted gas emissions. However, the enforcement will impose larger costs on ships or prolong their transit time. Hence, trade-offs must be assessed to reduce the price of compliance. To achieve this, this paper proposes a liner fleet model on a regular itinerary, in order to formulate an objective function to minimize its daily operating cost, with the aim to provide liner vessel fleets a theoretical guidance on how to combine the selected three options (slow steaming, scrubbers and lower sulfur fuel) while maintaining the same service frequency.